A bicategorical interpretation for relative Cuntz-Pimsner algebras - Meyer, Ralf; Sehnem, Camila F. (MATHEMATICA SCANDINAVICA, 2019)
We interpret the construction of relative Cuntz-Pimsner algebras of correspondences in terms of the correspondence bicategory, as a reflector into a certain sub-bicategory. This generalises a previous characterisation of absolute Cuntz-Pimsner algebras of proper correspondences as colimits in the correspondence bicategory.